Peningkatan Hasil Belajar Siswa Sekolah Dasar Melalui Penerapan Model Pembelajaran Examples Non Examples Berbantuan Media Audio Visual - Putu Yuli Krisniati; Putu Subawa; I Ketut Suparya (STAHN Mpu Kuturan Singaraja, 2020)
This study aims to determine the increase in science learning outcomes of elementary school students by applying the examples non examples learning model assisted by audio visual media. The subjects of this study were fifth grade students of Kubutambahan Elementary School No. 1, Kubutambah District, Buleleng Regency in the Academic Year 2019/2020 with a total of 28 students. This research is a classroom action research study consisting of two cycles. Student learning outcomes data were collected using test instruments. Research data were analyzed using quantitative descriptive analysis. The results showed that learning science by applying the examples non examples learning model assisted by audio visual media can improve the learning outcomes of students with excellent predicate science. Keywords: learning models, examples non examples and audio visual, learning outcomes